Optimal Control in Thermal Engineering - Badescu, Viorel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is the first major work covering applications in thermal engineering and offering a comprehensive introduction to optimal control theory, which has applications in mechanical engineering, particularly aircraft and missile trajectory optimization. The book is organized in three parts: The first part includes a brief presentation of function optimization and variational calculus, while the second part presents a summary of the optimal control theory. Lastly, the third part describes several applications of optimal control theory in solving various thermal engineering problems. These applications are grouped in four sections: heat transfer and thermal energy storage, solar thermal engineering, heat engines and lubrication.Clearly presented and easy-to-use, it is a valuable resource for thermal engineers and thermal-system designers as well as postgraduate students.
Introduction -- Functions optimization -- Elements of variational calculus -- Generalities concerning the optimal control problems -- The maximum principle (Pontryagin) -- The gradient method -- Dynamic programming (Bellman method) -- Heat transfer processes -- Heat exchangers -- Storage of thermal energy and exergy -- Heating and cooling processes -- Optimization of thermal insulation of seasonal water storage tanks -- Optimization of pin fin profiles -- Optimization of solar energy collection systems -- Flat-plate solar collectors. Optimization of absorber geometry -- Optimal time-dependent operation of open loop solar collector systems -- Optimal time-dependent operation of closed loop solar collector systems -- Optimal flow controllers -- Endoreversible heat engines -- Diesel engines -- Optimization of Daniel cam engines -- Photochemical Engines -- Optimization of one dimensional slider bearings. .
Keywords: Control engineering; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; System theory; Control theory; Control and Systems Theory; Engineering Thermodynamics, Heat and Mass Transfer; Systems Theory, Control; Thermodynamics